Early detection of the risk of chronic kidney disease based on eating and drinking behaviors in Kendari City Indonesia - Tasnim Tasnim; Imran Imran; Sugireng Sugireng; Nur Illiyyin Akib (Healthcare in Low-resource Settings, 2024)
The main purpose of this study is to analyze eating and drinking behavior that can be used for early detection of chronic kidney disease in Kendari City, Southeast Sulawesi. The research question is How do eating behavior and drinking water consumption affect protein urine, creatinine, and health status? This quantitative research used a cross-sectional study approach and recruited 136 respondents in Kendari City, Southeast Sulawesi, Indonesia from June to August 2023. The sampling technique is by accidental sampling technique. Eating behavior in calories and drinking water consumption are independent variables. Creatinine, protein urine levels, and health status are dependent variables. Data analysis using the chi-square, Kruskal Wallis H, linear regression, and ordinal regression of statistical tests. The daily drinking water consumption of less than 666 ml a day had a significant effect on protein urine levels by 19.6% and health status by 32.2%. However, it did not significantly affect urine creatinine levels. Total daily caloric intake did not significantly affect urine creatinine levels and protein urine, but it has a significant effect on health status by 8.2% especially total calorie intake which is less than 699 calories a day. Drinking water consumption of less than 666 ml a day and intake of calories less than 699 calories can be used as a basis for early detection of people at risk of developing chronic kidney disease.